The Role of Emotional Intelligence, the Teacher-Student Relationship, and Flourishing on Academic Performance in Adolescents: A Moderated Mediation Study - Chamizo-Nieto, María Teresa; Arrivillaga, Christiane; Rey, Lourdes; Extremera, Natalio (Frontiers in Psychology, 2021)
Educational context has an important influence on adolescents’ development and well-being, which also affects their academic performance. Previous empirical studies highlight the importance of levels of emotional intelligence for students’ academic performance. Despite several studies having analyzed the association and underlying mechanisms linking emotional intelligence and academic performance, further research including both personal and contextual dimensions is necessary to better understand this relation. Therefore, the purpose of this study was to deepen understandings of the effect emotional intelligence has on academic performance, examining the possible mediating role of flourishing and the moderating role of the teacher-student relationship. A convenience sample of 283 adolescents (49.8% female), aged 12–18 years (M = 14.42, SD = 1.12) participated in a cross-sectional study by completing self-report questionnaires measuring emotional intelligence (Wong & Law Emotional Intelligence Scale), flourishing (Flourishing Scale) and teacher-student relationship (Inventory of Teacher-Student Relationships), and reported their grades of the previous term on four mandatory subjects in the Spanish education curriculum. Results indicated that flourishing completely mediated the path from emotional intelligence to academic performance and that teacher-student relationship was a significant moderator in this model. Thus, in adolescents with worse teacher-student relationship, the association of emotional intelligence and flourishing was stronger than in adolescents with better teacher-student relationship. In turn, flourishing was positively associated with academic performance. These results suggest that it is crucial to foster better teacher-student relationship, especially in adolescents with low emotional intelligence, to positively impact their well-being and their academic performance.